2016
DOI: 10.1177/0883073816634858
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Lower Leg Adipose Tissue Distribution in Youth with Myelomeningocele

Abstract: Children with myelomeningocele have a high prevalence of obesity and excess fat accumulation in their lower extremities. However, it is not known if this is subcutaneous or intramuscular fat, the latter of which has been associated with insulin resistance and metabolic disorders. This study quantified lower leg bone, muscle and adipose tissue volume in children with myelomeningocele, classifying adipose as subcutaneous or muscle-associated. Eighty-eight children with myelomeningocele and 113 children without m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…19 Lorenzana et al 20 confirmed an increase in intramuscular fat in the lower limbs, which, although it is a risk factor for metabolic complications compared to subcutaneous fat deposits, may justify an increase in peripheral versus central FM%. Other studies 23 also confirmed peripheral FM localization, particularly in the lower limbs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 Lorenzana et al 20 confirmed an increase in intramuscular fat in the lower limbs, which, although it is a risk factor for metabolic complications compared to subcutaneous fat deposits, may justify an increase in peripheral versus central FM%. Other studies 23 also confirmed peripheral FM localization, particularly in the lower limbs.…”
Section: Discussionmentioning
confidence: 98%
“…Consistently with such lack of association, recent studies have demonstrated a greater lower limb FM in this population of patients. 20 It is also possible that the reduced number of patients in this category could have resulted in an underestimation of the relationship between both indicators.…”
Section: Discussionmentioning
confidence: 99%
“…En coincidencia con la falta de asociación, estudios recientes demuestran mayor localización de MG en los miembros inferiores en esta población de pacientes. 20 Existe también la posibilidad de que el reducido número de pacientes en esta categoría pudo haber subestimado la relación entre ambos indicadores.…”
Section: Discussionunclassified
“…DXA measurements are influenced by bone and body size and inhomogeneous fat distribution, ( 23,24 ) which are particularly problematic for children who are growing and for patient populations with short stature and high body fat as is common in SB. ( 14,25–27 )…”
Section: Introductionmentioning
confidence: 99%